Inhibition of DNA repair protein RAD51 affects porcine preimplantation embryo development. Issue 3 (March 2019) - Jin, Zhe-Long; Shen, Xing-Hui; Shuang, Liang; Kwon, Jeong-woo; Seong, Min-Jeong; Kim, Nam-Hyung
Abstract : Homologous recombination (HR) plays a critical role in facilitating replication fork progression when the polymerase complex encounters a blocking DNA lesion, and it also serves as the primary mechanism for error-free DNA repair of double-stranded breaks. DNA repair protein RAD51 homolog 1 (RAD51) plays a central role in HR. However, the role of RAD51 during porcine early embryo development is unknown. In the present study, we examined whether RAD51 is involved in the regulation of early embryonic development of porcine parthenotes. We found that inhibition of RAD51 delayed cleavage and ceased development before the blastocyst stage. Disrupting RAD51 activity with RNAi or an inhibitor induces sustained DNA damage, as demonstrated by the formation of distinct γH2AX foci in nuclei of four-cell embryos. Inhibiting RAD51 triggers a DNA damage checkpoint by activating the ataxia telangiectasia mutated (ATM)–p53–p21 pathway. Furthermore, RAD51 inhibition caused apoptosis, reactive oxygen species accumulation, abnormal mitochondrial distribution and decreased pluripotent gene expression in blastocysts. Thus, our results indicate that RAD51 is required for proper porcine parthenogenetic activation (PA) embryo development.